2004
DOI: 10.1007/s00223-004-0244-4
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Role of the SQSTM1 Gene in Sporadic Belgian Patients with Paget’s Disease

Abstract: A positional cloning effort in French Canadian families with Paget's disease of bone (PDB) resulted in the identification of a mutation in the sequestosome1 (SQSTM1) gene in a subset of both familial and sporadic PDB cases. This was confirmed in samples of mainly United Kingdom (UK) origin. In this study, we performed both mutation analysis and association studies in order to evaluate the role of this gene in a collection of isolated Belgian PDB patients. A mutation in the SQSTM1 gene was found in only 6 of 11… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
46
1
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 37 publications
0
46
1
1
Order By: Relevance
“…p62, as noted earlier, is an adaptor protein that binds ubiquitin and plays an important role in regulating NFjB signaling [69] as well as autophagy [70][71][72]. Current evidence suggests that mutations of SQSTM1 occur in 40-50 % of patients with a familial history of PDB and 2.5-10 % of ''sporadic'' PDB cases [60,65,66,73,74]. Virtually all of the PDB-causing mutations cluster in the UBA domain, and most prevent or A427D Yes Gennari et al [16] a Two different mutations were reported at the genomic level, which both resulted in the same amino acid change.…”
Section: Sqstm1mentioning
confidence: 92%
“…p62, as noted earlier, is an adaptor protein that binds ubiquitin and plays an important role in regulating NFjB signaling [69] as well as autophagy [70][71][72]. Current evidence suggests that mutations of SQSTM1 occur in 40-50 % of patients with a familial history of PDB and 2.5-10 % of ''sporadic'' PDB cases [60,65,66,73,74]. Virtually all of the PDB-causing mutations cluster in the UBA domain, and most prevent or A427D Yes Gennari et al [16] a Two different mutations were reported at the genomic level, which both resulted in the same amino acid change.…”
Section: Sqstm1mentioning
confidence: 92%
“…Both are receptors for the RANKL and therefore play a major role in the regulation of osteoclastogenesis via NFjB signalling. On the other hand, no evidence could be obtained for the presence of genetic variants within the SQSTM1 gene influencing the risk for PDB (Beyens et al 2004). Very recently, Albagha et al (2010) performed a genome-wide association study (GWAS) mainly on the British population and found strong evidence for genetic risk factors around the CSF1 (colony stimulating factor 1) and OPTN (optineurin) genes and confirmed involvement of the TNFRSF11A gene.…”
Section: Introductionmentioning
confidence: 95%
“…(72,74) Diagnosis of PDB was based both on alkaline phosphatase measurements and radiologic/scintigraphic examinations. All patients were of Belgian origin.…”
Section: Belgian Populationmentioning
confidence: 99%